2020
DOI: 10.1155/2020/7509481
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture for the Postcholecystectomy Syndrome: A Systematic Review and Meta‐Analysis

Abstract: Background. Postcholecystectomy syndrome (PCS) has become a common postoperative syndrome that requires systematic and comprehensive therapy to achieve adequate clinical control. Acupuncture and related therapies have shown clinical effects for PCS in many studies. However, systematic reviews/meta-analyses (SRs/MAs) for them are lacking. Objective. To evaluate the efficacy and safety of acupuncture in the treatment of PCS using randomized controlled trials (RCTs). Methods. Potentially eligible studies were sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 33 publications
(33 reference statements)
0
24
0
1
Order By: Relevance
“…The treatment principle thus should be based on regulating the flow of breath power, harmonizing the stomach, and descending adversely risen stomach breath power to stop vomiting [ 18 ]. A growing body of evidence confirms the great potential of acupuncture for digestive motility, secretion, and absorption to improve the quality of postoperative analgesia, promote recovery of postoperative gastrointestinal function, and reduce the incidence of PONV [ 19 , 20 ]. Thumbtack needling therapy is a type of floating or shallow stabbing in traditional acupuncture to promote the circulation of breath power and blood in the meridian defence.…”
Section: Discussionmentioning
confidence: 99%
“…The treatment principle thus should be based on regulating the flow of breath power, harmonizing the stomach, and descending adversely risen stomach breath power to stop vomiting [ 18 ]. A growing body of evidence confirms the great potential of acupuncture for digestive motility, secretion, and absorption to improve the quality of postoperative analgesia, promote recovery of postoperative gastrointestinal function, and reduce the incidence of PONV [ 19 , 20 ]. Thumbtack needling therapy is a type of floating or shallow stabbing in traditional acupuncture to promote the circulation of breath power and blood in the meridian defence.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1286 articles related to eight conditions were searched (Table 1). After reviewing the abstract and full text of the article, 17 systematic reviews and meta-analyses of the six conditions that met the inclusion criteria were finally included [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], and articles related to allergic rhinitis and chemotherapy-induced nausea and vomiting (CINV) did not meet the criteria for inclusion (Table 1).…”
Section: Results Of the Searchmentioning
confidence: 99%
“…Yin et al [27] found that acupuncture in combination with conventional treatment showed no statistical difference in pain reduction in Postcholecystectomy syndrome. The quality of the evidence for the overall outcomes was acceptable.…”
Section: Current Quality Of Evidencementioning
confidence: 99%
See 1 more Smart Citation
“… 15 20 So far, only one systematic review (SR) published in 2020 resulted that there is no statistical difference between acupuncture plus conventional medicine (CM) and single CM in reducing pain for patients with PCS. 21 In this case, a lack of SR to address the following pivotal questions: (1) is acupuncture effective in treating biliary colic with gallstones and (2) whether acupuncture an effective adjunctive therapy to CM for BC with gallstones. Thus, there is a chance for us to conceive a comprehensive review to determine the efficacy and safety of acupuncture for BC.…”
Section: Introductionmentioning
confidence: 99%